PENGARUH KOMPETENSI KARIR DAN PENGEMBANGAN KARIR TERHADAP KESUKSESAN KARIR KARYAWAN PT. JAYA TRADE INDONESIA REGION NUSA TENGGARA - Siga, Maria Karolina Yunita Weko; Se, Hyronimus (Universitas Bina Taruna Gorontalo, 2025)
This study seeks to identify and analyse the effect of both factors on career success. An associative strategy is used in this quantitative research. With a total of 39 participants, this study's research sample was representative of the population. This study makes use of quantitative data and employs multiple linear regression analysis techniques within the SPSS application. important for professional advancement, which in turn affects professional success. Achieving professional success is heavily influenced by both competently managing one's career and actively working to improve one's career. Approximately 65.4% of the career success variables may be explained by career competency and career growth variables, according to the computed coefficient of determination of 0.654, or 65.4%. At PT Jaya Trade Indonesia Nusa Tenggara Region, career competences and development account for 65.4% of the success that employees experience in their careers. Other factors that were not considered in this study account for the remaining 34.6%. To sum up, the success of employees' careers at PT Jaya Trade Indonesia Nusa Tenggara Region is influenced by their competencies in the workplace and their opportunities for professional development. The study found that employees' career success at PT. Jaya Trade Indonesia Nusa Tenggara Region is influenced by their career skills and career advances.